Discovering Techplomacy : A Comparative Study of Denmark and France - Addae, Nana; Rolenc, Jan Martin, 1980-; Stehlíková, Jana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
In this thesis, the discourse of Denmark and France technology ambassador offices are examined and placed in the context of the broader diplomatic practices and strategic objectives of their respective countries. The dominant International Relations paradigms of realism, liberalism, and conservatism provide the foundations to draw similarities and differences between the techplomacy approaches of Denmark and France.
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses